(untitled) (Journal of Global Arts Studies, 2025)
Background: Art game theory, as a theoretical approach that deeply explores the relationship between the essence of art and children’s nature, provides valuable insights for children’s aesthetic education. Its theoretical foundations include Friedrich Schiller’s “theory of play,” Immanuel Kant’s aesthetic theory, and John Dewey’s theory of experiential learning. The core concepts involve the commonality between art and play, the application of the spirit of play in art education, children’s subjectivity and creativity, and the educational value of art games. Objective: This study aims to explore the value of non-utilitarian art game theory in children’s aesthetic education and to propose educational strategies based on this theoretical perspective. Methods: Through case analysis and field research, several practical cases of children’s aesthetic education were selected to examine the specific applications and educational effects of art game theory in aesthetic learning contexts. Results: The findings indicate that art game theory plays a positive role in children’s aesthetic education and demonstrates significant educational value. Conclusion: Children’s aesthetic education and play share strong permeability and commonality in terms of origin, essence, characteristics, forms, and content. The core essence of children’s aesthetic education lies in the spirit of play, which emphasizes freedom, joy, and creativity—qualities that are highly consistent with the essence of aesthetic education. Therefore, integrating the spirit of play into children’s aesthetic education can effectively stimulate children’s artistic potential and promote their holistic development.